Formulation of a covalently bonded hydroxyapatite and poly(ether ether ketone) composite. (December 2018) - Hughes, Erik AB; Parkes, Andrew; Williams, Richard L; Jenkins, Mike J; Grover, Liam M
Spinal fusion devices can be fabricated from composites based on combining hydroxyapatite and poly(ether ether ketone) phases. These implants serve as load-bearing scaffolds for the formation of new bone tissue between adjacent vertebrae. In this work, we report a novel approach to covalently bond hydroxyapatite and poly(ether ether ketone) to produce a novel composite formulation with enhanced interfacial adhesion between phases. Compared to non-linked composites (HA_PEEK), covalently linked composites (HA_L_PEEK), loaded with 1.25 vol% hydroxyapatite, possessed a greater mean flexural strength (170 ± 5.4 vs 171.7 ± 14.8 MPa (mean ± SD)) and modulus (4.8 ± 0.2 vs 5.0 ± 0.3 GPa (mean ± SD)). Although the mechanical properties were not found to be significantly different (p > 0.05), PEEK_L_HA contained substantially larger hydroxyapatite inclusions (100–1000 µm) compared to HA_PEEK (50–200 µm), due to the inherently agglomerative nature of the covalently bonded hydroxyapatite and poly(ether ether ketone) additive. Larger inclusions would expectedly weaken the HA_L_PEEK composite; however, there is no significant difference between the flexural modulus of poly(ether ether ketone) with respect to HA_L_PEEK (p = 0.13). In addition, the flexural modulus of HA_PEEK is significantly lower compared to poly(ether ether ketone) (p = 0.03). Ultimately, covalent linking reduces hydroxyapatite particulate de-bonding from the polymeric matrix and inhibits micro-crack development, culminating in enhanced transfer of stiffness between hydroxyapatite and poly(ether ether ketone) under loading.